Effects of Real-World Problem Worksheets Integrated with Higher Order Thinking Skills on Physics Learning Outcomes: A Study of Industrial Engineering Students - Muhammad Syahrul Kahar; Muh Mawardi; Rahmatullah Bin Arsyad; Muhammad Fathurrahman; Sulkifli; Santi Rachman (Scientiae Educatia: Jurnal Pendidikan Sains, 2025)
This study aims to examine the effects of Real-World Problem Worksheets integrated with Higher Order Thinking Skills (HOTS) on students' physics learning outcomes in higher education. A pre-experimental research design with a one-group posttest-only configuration was employed as the methodological framework. Data were collected through a validated physics achievement test instrument specifically designed to assess student learning outcomes following the instructional intervention. The sampling procedure employed was cluster random sampling, with a total sample of 30 industrial engineering students from Universitas Muhammadiyah Sorong. The findings reveal that the mean student score reached 7.67, indicating a notable improvement in physics learning outcomes following the implementation of the Real-World Problem Worksheets. Statistical analysis using the t-test further demonstrated that the calculated t-value significantly exceeded the critical t-table value (t = 17.95 > t-table = 2.05), confirming that the implementation of Real-World Problem Worksheets integrated with HOTS produced a statistically significant improvement in students' physics learning outcomes. Furthermore, student response data indicated that the instructional intervention was received with highly favorable evaluations, reflecting strong learner acceptance and engagement with the worksheet-based approach. These findings collectively suggest that the integration of real-world contextual problems with HOTS-oriented worksheets constitutes a promising and empirically supported pedagogical strategy for enhancing physics learning outcomes in undergraduate science and engineering education.